"We Can See a Bright Future": Parents' Perceptions of the Outcomes of Participating in a Strengths-Based Program for Adolescents with Autism Spectrum Disorder. - Lee, Elinda Ai Lim; Black, Melissa H.; Falkmer, Marita; Tan, Tele; Sheehy, Louise; Bölte, Sven; Girdler, Sonya (Journal of Autism & Developmental Disorders, 2020)
Autistic individuals often possess strengths and abilities. Despite these strengths, employment outcomes for this population remain low. Strengths-based programs, focusing on developing skills in a supportive environment, may enable autistic adolescents to more effectively prepare for the workforce. This study explores the principal components and associated outcomes of a strengths-based program designed to support autistic children and adolescents to develop interests and skills in Science, Technology, Engineering, Arts, and Mathematics. The baseline results of 52 parents of autistic youth participating in a 3-year longitudinal survey study were explored, with results showing that according to parents the program positively impacted participants' sense of belonging, confidence and self-esteem, health and well-being, social relationships and interactions, and activities and participation.